THE IMPLEMENTATION OF MEDIATION STRATEGIES IN SCHOOL CONFLICTS IN THE CLASSROOM. - Lilly Leyla Marínez Angulo (LÍNEA IMAGINARIA, 2025)
Conflict is inherent to the relationships that are established between human beings in different environments, including educational institutions, and reflection on how they are addressed is a constant concern and requires pedagogical innovations that focus on school mediation strategies for the improvement of relationships within the classroom. Therefore, this documentary review article aims to identify how school conflicts are being handled in the classroom and whether literature is a strategy that is being considered for this purpose. Therefore, it takes into account the description of master's theses of the last five years for a total of 31 theses consulted in repositories of national (Colombia) and international universities, through the implementation of the Prisma flowchart and the Casp checklist with categories that highlight the study, its theoretical and methodological contributions and main findings. The ideas put forward provide a theoretical and practical guideline that allows exposing the management of school conflict from several dimensions. Theoretically, the socioemotional component as a fundamental reference, methodologically, action research as an option for immediate intervention. With respect to the literary approach, this is presented in various ways in the use of stories, lyrical texts, fables, films, which in their real functionality show that